Drug-Induced Movement Disorders - Pandey, Sanjay; Pitakpatapee, Yuvadee; Saengphatrachai, Weerawat; Chouksey, Anjali; Tripathi, Madhavi; Srivanitchapoom, Prachaya (Seminars in Neurology, 2023)
Drug-induced movement disorders (DIMDs) are most commonly associated with typical and atypical antipsychotics. However, other drugs such as antidepressants, antihistamines, antiepileptics, antiarrhythmics, and gastrointestinal drugs can also cause abnormal involuntary movements. Different types of movement disorders can also occur because of adverse drug reactions. Therefore, the important key to diagnosing DIMDs is a causal relationship between potential offending drugs and the occurrence of abnormal movements. The pathophysiology of DIMDs is not clearly understood; however, many cases of DIMDs are thought to exert adverse mechanisms of action in the basal ganglia. The treatment of some DIMDs is quite challenging, and removing the offending drugs may not be possible in some conditions such as withdrawing antipsychotics in the patient with partially or uncontrollable neuropsychiatric conditions. Future research is needed to understand the mechanism of DIMDs and the development of drugs with better side-effect profiles. This article reviews the phenomenology, diagnostic criteria, pathophysiology, and management of DIMDs.
Keywords: movement disorders; tardive syndromes; antipsychotics